Transformasi Digital Keuangan UMKM Melalui Pendampingan Aplikasi SIAPIK - Wulan Wahyu Ningrum; Yulia Yulia; Sabirin Sabirin; Luqman Luqman; Hani Meilita Purnama Subardi; Izza Karunia Putri; Ari Yunaldi; Yuyun Yuliana; Saipullah Saipullah; Amir Prihatin; Musa Amin (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to improve financial literacy and the adoption of digital financial accounting among micro, small, and medium enterprises in Pontianak City and Kubu Raya Regency. The method used was face-to-face active participatory assistance over eight weeks through collaboration between academics and practitioners. The intervention was carried out in five structured stages ranging from problem identification, cash separation education, installation of financial recording applications, technical guidance on transaction entry, to independent monitoring of 45 business owners as target partners. The results indicated a significant improvement in the financial governance of the business actors. The majority of partners successfully separated personal and business cash, became proficient in digital daily transaction entry, and were able to independently download automated profit and loss statements and financial position reports. This activity successfully transformed financial behavior from manual to structured digital record-keeping. Practically, the availability of accountable financial reports enhances the administrative readiness of business owners to access formal financing and strengthens local economic resilience.